Hydrogel nanoparticle encapsulated plasmid as a suitable gene delivery system - Rafiee, A.; Riazi-Rad, F.; Alimohammadian, M.H.; Havaskary, M.; Fatemi, S.M.R.; Pakpoor, B. (Цитология и генетика, 2015)
To facilitate the delivery of genetic material, the use of appropriate carriers such as polymers is necessary. Nanoparticles comprising of chitosan-alginate polymers were formed through pregel preparation method. Chi/Alg nanoparticles had a mean Z-Average diameter of 161.8 nm and mean zeta 29.3 mV, respectively. The ability of plasmid-complex in preventing DNA migration showed Chi/Alg nanoparticles have great capacity to maintain plasmid. The efficiency of nanoparticles for transfection of pEGFP-N1 plasmid in the cultured HEK 293 cells was measured by flow cytometry. Cell viability assays indicated that nanoparticles had no toxic effect on HEK 293 cells after 4 or 24 h. Our suitable candidate for gene delivery would be alg/chi nanoparticles.